IMPLEMENTASI ALAT MONITORING HOUR METER PADA MESIN LATHE BERBASIS INTERNET OF THINGS - Qory Hidayati; Nurwahidah Jamal; Erick Sorongan; Nindha Anggana Raras (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Along with the increasing demand for remanufacturing, to support the production process several types of machines are used. To support the manual machine production process, companies such as lathe machines also need a tool to monitor machine hour meters remotely so that several potential problems that arise can be resolved. This research uses quantitative methods which aim to find and design tools systematically. This research uses the RTC DS1307 sensor to calculate working time on the machine, the PZEM 004t sensor as a machine motor current meter, along with the Nextion LCD output and website. In general, this Hour Meter monitoring tool is used to find out how long the machine has been working, daily productivity on the machine is 3 hours 36 minutes, for machine utility it is 12 hours 13 minutes in 5 working days of the machine and also the condition of the machine when it is in Off (Idle) status. Ampere Nan A, Voltage Nan V and Load condition have Unload status. When On (Run) the Ampere status changes from Nan A to 8.47 or more, the voltage is 226.50v or more and the Load Condition becomes Load.